CLINICAL EVALUATION OF SHATAPUSHPA SHATAVARI CHURNA AND O.C. PILLS IN THE MANAGEMENT OF ARTAVA KSHAYA W.S.R. TO CERTAIN MENSTRUAL DISORDERS - Bediskar, *Nilesh Y.; M. Yennawar, Sandhya (International Journal of Ayurveda and Pharma Research, 2017)
A randomised control clinical trial was carried out on 60 Artava Kshaya (irregular, scanty and painful menses) patients aged between 18 and 40 years having complaints of irregular, scanty and painful menstruations. The patients were registered from OPD of CSMSS Ayurved Rugnalaya & Research Centre, Aurangabad. Divided into 2 groups. They were administrated Shatapuspa and Shatawari churna (group A) and OC pill (group B) for three months in a dose of 5 g daily with cow Ghrita and Guda; OC pills (Mala N) once in a day as per standard schedule. The specific investigations were done in order to exclude congenital anomalies, endometritis, endocrine disorders, diabetes and heart disease. The clinical assessment was carried out in 3 intervals 30 days apart. It is inferred that the study shows the effect of both treatments were significant in clinical study. In group A, none of the patient showed excellent improvement in Artava Kshaya, while moderate improvement was observed in one (3.33%) patient, mild improvement was observed in 25 (83.25%) patients and 4 (13.32%) of the patients showed ineffective improvement after treatment. In group B, none of the patient showed excellent improvement in Artava Kshaya, while moderate improvement was observed in 2 (6.66%) patients, mild improvement was observed in 25 (83.25%) patients and 3 (9.99%) of the patients showed ineffective improvement after treatment. The Shatapushpa Shatavari Churna is more effective on Yoni Vedana, Artava strava Pramana and Artava strava kalvavadhi.-Both Shatapushpa Shatavari Churna and O.C. pill are effective on and duration between two Artava Darshana but O.C. pill is comparatively more effective.